Smart Clove Oil Distillation System using IoT and Ultrasonic Sensors - As'ad, Ihwana; Rahmatullah, Andi Muhammad; Abdullah, Syahrul Mubarak; Fahmi, Fahmi; Pakka, Hariani Ma'tang; Andiyan, Andiyan (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Traditional clove essential oil distillation remains inefficient due to manual labor dependency, imprecise oil-water separation, and inconsistent product quality. Addressing these limitations, this study aims to design and develop a smart, Internet of Things (IoT)-based system named AquaClove to automate and optimize the distillation process. The system integrates an ESP32 microcontroller, ultrasonic sensors, and solenoid valves, enabling precise fluid level detection and automated oil-water separation. Using the Arduino IoT Cloud, the system supports real-time monitoring and remote control, enhancing operational transparency and scalability. results indicate that the system achieved a 32% reduction in total distillation time (from 4.2 to 2.9 hours), 66.7% reduction in labor requirements (from 3 to 1 personnel), and 66.7% reduction in oil loss per 10-liter batch (from 0.6 L to 0.2 L). The ultrasonic sensors consistently detected liquid levels with an average measurement deviation of less than ±2 mm, while solenoid valves responded within 0.8 seconds of command input. These outcomes demonstrate significant improvements in process efficiency, separation precision, and system responsiveness. Furthermore, the modular container design promotes gravity-assisted separation, enhancing energy efficiency and reducing mechanical complexity. The remote monitoring feature allows users to access real-time data on fluid levels and system status, ensuring reliable operation with minimal manual supervision. AquaClove thus demonstrates how integrating ultrasonic sensing and IoT technologies can modernize traditional agricultural processes. This study contributes a scalable and sustainable solution to the essential oil industry, particularly in small- and medium-scale clove oil production.